Expression of Xyloglucanase (AaXEG2) in Open-field-grown Poplars - Haruka Iizuka; Tomomi Kaku; Toru Taniguchi; Manabu Kurita; Ken-ichi Konagaya; Katsuaki Ishii; Teiji Kondo; Kei’ichi Baba; Rumi Kaida; Teruaki Taji; Yoichi Sakata; Takahisa Hayashi (Masyarakat Peneliti Kayu Indonesia, 2012)
The transgenic expression of Aspergillus aculeatus xyloglucanase with 35S promoter, which has been maintained in greenhouse-grown transgenic poplars for 10 years, was assessed to determine their expression level in open-field-grown poplars. This level was slightly decreased in the poplars grown in fertile soil for four years, and there were proportionatel y decreased levels of xyloglucanase activity among their tissues, in which the shoots exhibited slightly lower specific activities than was observed in the leaves and roots. Xyloglucan content was greatly decreased in the walls of the tissues in the transgenic lines, although the degradation levels of xyloglucan were slightly lower for the poplars grown in fertile soil than for those grown in non-fertile soil. The results showed that the level of expression, together with xyloglucan degradation in their walls, was decreased for the poplars grown in fertile soil.